Analisis Kondisi Existing Jalan Rel Blitar – Malang Berdasarkan Nilai Track Quality Index: Analysis of the Existing Condition of the Blitar – Malang Railway Based on the Track Quality Index - Santoso, Toni Budi; Al Zakina, Bella Lutfiani; Ikhwan, Mohammad Zainul (Jurnal Rekayasa Infrastruktur HEXAGON, 2023)
The value or output in the form of a number from the measurement results of the measuring train which can provide information on the quality of the railroad track that is passed on a railroad segment is called the Track Quality Index (TQI). The TQI value is obtained from the sum of 4 measurement parameters, namely track width, lift, power and height. The higher the TQI value indicates the higher the level of rail damage. Several train accident investigation reports, especially derailments, were influenced by poor TQI values. The government has limitations in obtaining TQI values ​​due to the limited number of measuring trains it has and operations are periodic. Therefore, alternatives are needed to predict TQI values ​​other than measuring train operating data. The method used to solve this problem is direct measurement with a measuring train for a track width of 1067 mm. Then an analytical calculation is carried out to find the average deviation, variance and standard deviation. The calculation results show an average deviation of 93.78 and an average standard deviation of 37.81. Based on the provisions for grouping TQI values, a high TQI value is taken, namely the average deviation with track conditions is at a value of 4. Taking a higher number is indicated for the safety of railway operations, the higher the worse the condition of the railway, so high frequency maintenance of the railway is required.